2020
DOI: 10.1021/acsbiomaterials.0c00280
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Layer for Ni Detection in Water Created by Immobilization of Bioengineered Flagellar Nanotubes on Gold Surfaces

Abstract: The environmental monitoring of Ni is targeted at a threshold limit value of 0.34 μM, as set by the World Health Organization. This sensitivity target can usually only be met by time-consuming and expensive laboratory measurements. There is a need for inexpensive, field-applicable methods, even if they are only used for signaling the necessity of a more accurate laboratory investigation. In this work, bioengineered, protein-based sensing layers were developed for Ni detection in water. Two bacterial Nibinding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Based on the results presented in this work, the advantageous properties of the previously published nickel sensing layer 1 , and in comparison with other protein-based sensors created for arsenic detection, we can conclude that mutant flagellins containing toxic metalion binder peptide motifs, which are well designed and therefore…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Based on the results presented in this work, the advantageous properties of the previously published nickel sensing layer 1 , and in comparison with other protein-based sensors created for arsenic detection, we can conclude that mutant flagellins containing toxic metalion binder peptide motifs, which are well designed and therefore…”
Section: Discussionmentioning
confidence: 53%
“…In that work, various Ni-binding flagellin variants were constructed by mutations in the D3 domain or replacement with a histidine-rich polypeptide motif. We demonstrated that by immobilizing nanotubes built from mutant flagellins by in vitro polymerization on the surface of biochips, a Ni(II) ion concentration of 1 μM could be detected, which is close to the maximum allowable concentration (0.34 μM) 1 . These results prompted us to create novel flagellin-based sensor layers that, when incorporated into a biosensor, can be suitable for monitoring arsenic pollution in natural waters.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations